Fibrin Deposition and Growth of Connective Tissue - Triantaphyllopoulos, D. C; Triantaphyllopoulos, E (Thrombosis and Haemostasis, 1969)
Inhibition of coagulation by the 25-50% ammonium sulfate fraction of lysed fibrinogen or by heparin delays the formation of adhesions between polyvinyl sponges and peritoneum and retards the invasion of the sponges by connective tissue.